Magnetite‐Free Sn‐Doped Hematite Nanoflake Layers for Enhanced Photoelectrochemical Water Splitting. Issue 11 (1st June 2022) - Ahn, Hyo‐Jin; Kment, Stepan; Yoo, Jeong Eun; Truong Nguyen, Nhat; Naldoni, Alberto; Zboril, Radek; Schmuki, Patrik
Abstract: In the present work, we report a preparation strategy for hematite phase‐pure photoanodes consisting of Sn‐doped hematite nanoflakes/hematite thin film bilayer nanostructure (Sn‐HB). This approach is based on a two‐step annealing process of pure iron films deposited on fluorine doped tin oxide (FTO) substrates by advanced magnetron sputtering. While the high density hematite ultrathin nanoflakes (HNs) with detrimental iron oxide layers (Fe3 O4 and/or FeO) are generated during the first annealing step at 400 °C for two hours, the second thermal treatment at 800 °C for 15 minutes oxidises all the undesired iron oxide phases to a photoactive hematite layer as well as is providing efficient Sn doping of a drop‐casted SnCl4 in order to increase the conductivity. The optimized Sn‐HB shows an around 11 times higher photocurrent density (0.71 mA cm −2 at 1.23 VRHE ) compared with a reference hematite photoanode produced from iron foil under the same conditions. Abstract : Sn‐doped hematite nanostructure composed of nanoflakes and thin film bilayer has been synthesized by using a two‐step annealing process from pure iron film, which shows excellent performance as photoanode in water splitting. The detrimental iron oxide phases (Fe3 O4 and/or FeO), which cause the charge recombination, have been successfully removed, resulting from optimized process.